Editorial - Dang, Raman (Indian Journal of Pharmacy Practice)
Clinical Pharmacy is a very important committed job. Clinical pharmacists work directly with physicians, other health professionals, and patients to ensure that the medications prescribed for patients contribute to the best possible health outcomes. Clinical pharmacists practice in health care settings where they have frequent and regular interactions with physicians and other health professionals, contributing to better coordination of care.